1998
DOI: 10.1097/00005344-199801000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Protection Afforded by Nicorandil and Ischaemic Preconditioning in a Rabbit Infarct Model In Vivo

Abstract: We previously showed that preoperative nicorandil, a hybrid potassium channel opener and nitrate compound, conferred cardioprotective effects in a hypoxia/reoxygenation model of isolated human atrial muscle by using functional recovery as an end point, and that ischaemic preconditioning surprisingly abolished the protection afforded by nicorandil. In view of this paradoxic result, this study was undertaken to assess whether ischaemic preconditioning influences any protective effect of nicorandil by using infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 22 publications
4
63
0
3
Order By: Relevance
“…Its cardioprotective action has been reported in various animal models 17,18 and in humans. [19][20][21][22][23][24][25] The present study investigated whether or not nicorandil affects ischemic preconditioning during PTCA.…”
mentioning
confidence: 98%
“…Its cardioprotective action has been reported in various animal models 17,18 and in humans. [19][20][21][22][23][24][25] The present study investigated whether or not nicorandil affects ischemic preconditioning during PTCA.…”
mentioning
confidence: 98%
“…Cardioprotection by the use of K-ATP channel openers: The cardioprotective effect of Nic is known to be associated with a pharmacological preconditioning effect in acute ischemia. 3,20,21) Although two possible mechanisms for this cardioprotective effect have been discussed, a reduction in the intracellular calcium overload by shortening the action potential duration through sarcolemmal K-ATP channel opening and the protection of mitochondrial function by opening the mitochondrial K-ATP channels, the latter has been more emphasized in recent reports because the effect of Nic on mitochondrial K-ATP channels is much stronger than that on sarcolemmal K-ATP channels. [21][22][23] Therefore, Nic is now mainly viewed as a mitochondrial K-ATP channel opener, at least at the clinical dose.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that shortening the myocardial action potential duration in the acute phase of myocardial injury may result in later myocardial protection possibly through the reduction in the intracellular calcium overload. 4,20,21) In contrast, Nic affected neither the myocarditis nor MAPD in the acute phase, but the Nic treatment resulted in better ventricular function in the chronic phase. Because the redox state of the mitochondria improved in the EAM+Nic groups in comparison with the control EAM group, protection of the mitochondrial function during the acute phase seemed to be the mechanism of the cardioprotection by Nic, similar to the acute ischemia model.…”
Section: Mechanisms Of the Cardioprotection Of K-atp Channel Openersmentioning
confidence: 93%
“…However, previous studies have shown that antioxidant drugs improve post-ischemic cardiac dysfunction in isolated hearts. 22,23 Therefore, because nicorandil has been reported to have many beneficial effects, such as opening the mitochondrial KATP channels, 4,5 inhibiting apoptosis, 24 inhibiting platelet aggregation, 25 direct preservation of mitochondrial function, 26 and coronary capillary architecture and volume, 27 besides free radical scavenging effects, it is still difficult to say whether the decrease in 2,3-DHBA concentration is the main cause of the attenuation of ischemia -reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%